(untitled) (Bangabandhu Sheikh Mujib Medical University Journal, 2016)
Background: Tetanus remains one of the major public health hazards of the developing world. Mortality is much lower in the developed world because of the availability of facilities, unlike in most developing countries’ Objectives: This study was aimed to determine the outcome of tetanus patients admitted in infectious disease unit of Rangpur Medical College Hospital. Methods: A total of 91 cases of tetanus patients were seen in the 18 month period with a mean of 5 cases per month; they are diagnosed and managed for tetanus in the medical wards from January 2011 to June 2012. The data were retrieved from their case records and analyzed. Results: There were thirty one deaths, accounting for an overall mortality of 34.16o.Total fifty six patients were cured among which sixteen (17.67%) were cured with complication and four (4.4%) patient were absconded. Mortality was high 45.84% (11 patients out of 24) ?40 years age, whereas low 29.85 (20 patient out of 87) in <40 yea15 age (45.84% vs 29.85%). Mortality rate was also higher among female than male patients (34.66% vs 33.85%). Farmers experienced more death than non-farmer (4l.l8% vs 29-82%, P<0.05). Mortality was higher in patients who had not received any medical treatment for their wound than in patients who had received it for their wound (52.78% vs 21.81%, p<0.05). Patients with short incubation period of less than one week had higher mortality in comparison with those who had incubation period more than one week (53.33% vs 23.25%, P<0’05). Of the 91 patients, fifty six (64.34%) were alive, though four remained in a persistent vegetative state due to tetanus toxin-induced brain damage and another two required a below knee amputation of the left leg. Hence, 40 were discharged well and 16 were discharged with permanent disabilities. Conclusion: The case fatality rate of tetanus has remained consistently high in the medical college. Factors that were significantly associated with high mortality included older age, and incubation period of less than 7 days. It is recommended that preventive immunization against tetanus be given to all Bangladeshis with secondary vaccination at adulthood.